Karakteristik Permen Karamel Susu Rendah Sukrosa Dengan Penambahan Isomalt Sebagai Bahan Pemanis - Weluz, Georgiana Patricia; Pratiwi, I Desak Putu Kartika; Putra, I Gede Arie Mahendra (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 3 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i03.p05, 2024)
Milk caramel candy is a soft candy made from milk and sugar. Using alternative sweeteners such as isomalt as a substitute for sucrose is expected to reduce the total sugar of milk caramel candy This study aimed to determine the effect of the sucrose and isomalt ratio on the characteristics of milk caramel candy, and to determine the right ratio of sucrose and isomalt to produce milk caramel candy with the best characteristics. A completely randomized design was employed with 6 treatments of sucrose and isomalt ratio: 100:0, 80:20, 60:40, 40:60, 20:80 dan 0:100. Parameters observed were moisture content, ash content, total sugar, reducing sugar content, hedonic (color, texture, taste, and overall acceptance), and stickiness intensity, hardness intensity, and sweetness intensity. The treatments affected moisture content, ash content, total sugar, reducing sugar content, as well as color, texture, taste, stickiness, hardness and sweetness. Milk caramel candy with a ratio of 40 percent sucrose and 60 percent isomalt has the best characteristics, with a moisture content of 6.55 percent, ash content of 1.37 percent, total sugar of 59.41 percent, reducing sugar content of 11.15 percent. In terms of sensory acceptance, the color was rated as slightly liked, the texture as liked, the taste as liked, and the overall acceptance as slightly liked. Increasing the isomalt proportion in the formulation effectively reduced the total sugar and reducing sugar content of the milk caramel candy. This study highlights an innovative approach to substituting sucrose in caramel candy production. Keywords: isomalt, low sugar, milk caramel candy, sucrose